2015
DOI: 10.1111/jerd.12133
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence That Bioactive Cements Occlude Artificial Marginal Gaps

Abstract: The results of this laboratory study, although preliminary in nature, suggest a new functional property for bioactive dental materials, namely the ability to significantly improve marginal stability with tooth/restorative material interface. Such behavior in a restorative material could improve the survival and serviceability of dental restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Thus, an acidic pH induced by glass ionomers presumably describes the inability of glass ionomers to support apatite precipitation. Our findings are in agreement with a previous study which showed that MTA, as a calcium silicate cement, exhibited rapid closure of artificial marginal gaps compared with calcium aluminate‐glass ionomer, whereas conventional glass ionomer and resin‐modified glass ionomers did not reveal gap closure capability .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, an acidic pH induced by glass ionomers presumably describes the inability of glass ionomers to support apatite precipitation. Our findings are in agreement with a previous study which showed that MTA, as a calcium silicate cement, exhibited rapid closure of artificial marginal gaps compared with calcium aluminate‐glass ionomer, whereas conventional glass ionomer and resin‐modified glass ionomers did not reveal gap closure capability .…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, in a comparative study done by Jefferies et al [50] to explore whether bioactive dental cement has the ability to seal the marginal gap in comparison to other classes of dental cements. They pointed out that Ceramir can occlude the marginal gap areas.…”
Section: Discussionmentioning
confidence: 99%
“…Since apatite is the most stable mineral of calcium and phosphate at a pH over 8, the precipitated material was assumed to be apatite 11 . The other clinical function of this precipitated hydroxyapatite is to occlude an open cement gap at a crown margin 12 . In a laboratory study, discs of human dentin and calcium aluminate cement (Ceramir Crown and Bridge) were separated by a mylar film of 50 μm and placed in a phosphate containing solution for up to 8 months.…”
Section: Introductionmentioning
confidence: 99%
“…The gap between the discs was observed with light microcopy, and the calcium aluminate cement specimens were capable of filling the cement gap with an apatite precipitate. 12 A calcium aluminate-based cement was shown to precipitate surface hydroxyapatite, whereas a glass ionomer and a resinglass ionomer hybrid (Activa Bioactive Restorative) material did not. 10,13 Aside from hydroxyapatite deposition, bioactive cements have also been credited with releasing ions that may help prevent demineralization of surrounding tooth structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation